Análise da influência do nível de atividade física com o polimorfismo do gene FTO, e a relação com a modulação autonômica cardíaca em estudantes de uma escola pública de São Luís do MA. - RABÊLO, Luís Gustavo Dias (2023)
Objective: To analyze the influence of physical activity level with FTO gene polymorphism, and its relationship with cardiac autonomic modulation in students from a public school in São Luís, MA. Materials and methods: A descriptive, quantitative, and cross-sectional field research was conducted with 288 students of both sexes, aged between 11 and 18 years old, enrolled in the public school system in the city of São Luís, MA. They were divided into four groups (AA+AT act, AA+AT sed, TT act, and TT sed), taking into account the genotypes AA, AT, and TT. Physical activity level, body mass index, anthropometric measurements, oral cell collection, DNA extraction, and PCR to identify the FTO gene polymorphism, blood pressure recording, and heart rate variability recording were evaluated. Data were analyzed using the JAMOVI program. The statistical treatment consisted of the Shapiro-Wilk Normality test, one-way ANOVA with Tukey's post-hoc test. Data were considered statistically significant when the pvalue was less than <0.05, at a 95% confidence interval. In addition, the ChiSquare test was used to analyze allelic distribution. Results: There were no significant differences between groups for SBP, DBP, and HR variables. For weight, TT sed individuals compared to TT act group (53.50 ± 9.61) showed a statistically significant difference and a higher mean value than all other groups. Regarding BMI, there were no significant differences in any group. CC showed significantly higher results for TT sed group compared to TT act (68.19 ± 6.89). For NAF, sedentary individuals, both AA+AT and TT (370.16 ± 169.78) and (341.87 ± 152.79) obtained significant differences compared to active groups, demonstrating a lower level of physical activity (p<0.001). Regarding heart rate variability, the results showed no statistically significant differences between groups for time-domain variables [RR(ms), RMSSD(ms), SDNN(ms), PNN50(ms)] and frequency-domain variables [BF(ms2), AF(ms2), BF (%), AF(%) and BF/AF]. Conclusion: The research demonstrated that the physical activity level in students who have the FTO gene polymorphism does not affect cardiac autonomic modulation.